A reflection on the morality of ownership of genetic material - De Carvalho, Candice Lee (My University, 2011)
The question of ownership of genetic material is highly relevant to medical ethics at this point in our history. What has become a major debate is how DNA can, and if it ought to be commoditised; and how and if individuals can keep their genetic information private, or whether it ought to be shared with all. In this research report I question whether genetic information is exceptional when compared with other medical or health-related information. The Kantian view of commoditisation of the body and human dignity is given along with some of the most prominent views on self-ownership. Patenting and genetic biobanking have received much attention in recent years, I focus on these issues and moral questions that surround these practices. The idea of genetic information as a common and natural 'resource' is discussed. If it is indeed a common heritage for all, how ought individuals, populations, researchers and funders to relate to genetic information? I briefly examine what some communities and cultures may have to say about genetic information and I attempt to tie all these varying perspectives together. I find that it is not ownership per se that is often the subject of dispute, but how those who happen to have control over that information share it. I present a possible maxim to guide the sharing of genetic information with others; that patenting does not necessarily amount to an affront to human dignity in the Kantian sense and that inter-cultural perspectives on genetic information may differ significantly. I conclude that how genetic material is shared, or not shared and why seems to depend more on the population in question at any given time and its social, political and economic structures than on the question of ownership per se.
Keywords: Bioethics; Genetics